Synthesis of Heterocyclic pendant on poly( vinyl alcohol) - Entesar Obed.Al-Tamimi; Hizoom Mola Al-mayiah (Al-Qadisiyah Journal of Pure Science, 2018)
Reaction of Poly vinyl alcohol(PVA) with adipoly dichloride to produced new ester- acid chloride is very active to react with hydrazine hydride, then the producs treated with 40% Potassium hydroxide(KOH) in Carbon disulphide(CS2) and heated for 6 hours with reflux to yield heterocyclic (3- Thio pyrazole) on PVA. The prepared polymers were identified by FF-IR and H-NMR spectra and some physical properties such as softening armelting points , solubirity , and thermes stability were studied.